GUI bloopers 2.0 : common user interface design don'ts and dos - Johnson, Jeff (Consultant) (Morgan Kaufmann series in interactive technologies., 2008)
"GUI Bloopers 2.0 looks at user interface design bloopers from commercial software, Web sites, Web applications, and information appliances, explaining how intelligent, well-intentioned professionals make these mistakes - and how you can avoid them."--Jacket